2021
DOI: 10.1038/s41598-021-93417-z
|View full text |Cite
|
Sign up to set email alerts
|

Solar forcing of early Holocene droughts on the Yucatán peninsula

Abstract: A speleothem record from the north-eastern Yucatán peninsula (Mexico) provides new insights into the tropical hydro-climate of the Americas between 11,040 and 9520 a BP on up to sub-decadal scale. Despite the complex atmospheric reorganization during the end of the last deglaciation, the dominant internal leading modes of precipitation variability during the late Holocene were also active during the time of record. While multi-decadal variations were not persistent, Mesoamerican precipitation was dominated by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Available paleoclimate reconstructions illustrate the amplitude and extent of the environmental changes induced by the 8.2 ka event, but the lack of high-resolution proxy records during the early Holocene, especially in the tropics (Lechleitner et al, 2017; Parker and Harrison, 2022; Warken et al, 2021), limits our understanding of the temporal evolution of the event and the underlying dominant response mechanisms beyond the extratropical North Atlantic. Here we present geochemical results from a well-dated stalagmite (PR-PA-1), collected in Palco Cave, Puerto Rico, that grew continuously through the 8.2 ka event and provides insights on the event’s temporal structure and spatial impact on the tropical Atlantic at sub-decadal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Available paleoclimate reconstructions illustrate the amplitude and extent of the environmental changes induced by the 8.2 ka event, but the lack of high-resolution proxy records during the early Holocene, especially in the tropics (Lechleitner et al, 2017; Parker and Harrison, 2022; Warken et al, 2021), limits our understanding of the temporal evolution of the event and the underlying dominant response mechanisms beyond the extratropical North Atlantic. Here we present geochemical results from a well-dated stalagmite (PR-PA-1), collected in Palco Cave, Puerto Rico, that grew continuously through the 8.2 ka event and provides insights on the event’s temporal structure and spatial impact on the tropical Atlantic at sub-decadal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…The analytical setup and measurement protocol of trace elements follows the method described by Warken et al. (2021). The analysis of trace elements was performed at the Institute of Environmental Physics, Heidelberg University.…”
Section: Methodsmentioning
confidence: 99%
“…The δ 234 U0 value is influenced by several processes, such as the alpha-recoil process, host rock dissolution, and redox-behavior of Uranium [7][8][9][10] . In general, the δ 234 U0 value of secondary carbonates from the northern YP is close to secular equilibrium [11][12][13] and hence lower than the δ 234 U0 value of seawater (146.8±0.1‰ 14 ). In a recent study from southwest Nevada, it was suggested that even under dry conditions (e.g., during periods of a low water table), alpha-recoil causes excess 234 U to accumulate in damaged crystal lattice sites and/or on fractured surfaces of the bedrock and sediments, which may then be 'captured' as the water table returns 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The measured δ 234 U values vary from 15.1 ± 1.2 to 59.9 ± 4.4‰, and the 230 Th/U ages range from recent to as old as 96 ky. To estimate the potential influence of initial (either detrital or freshwater derived) excess 230 Thxs on the 230 Th/U age, a first order correction was applied. Here, we assume one single source of contamination with a moderately elevated detrital ( 230 Th/ 232 Th) activity ratio of 2 ± 1, which is based on previous observations from speleothems of cave sites on the YP and the Caribbean realm 11,12,[30][31][32][33][34] . When using this correction model, the corrected ages for the measured Hells Bells samples range from 95.81 ± 0.52 ky to modern.…”
mentioning
confidence: 99%